Root accumulation and efficient translocation of steroids in mangrove plants: Implications for an overlooked coastal reservoir - Ji-Xun Chen; Nian-Nian Wu; Shan Liu; Yuan Liu; Qin-Ge Zhou; Qing-Song Yang; Juan Ling; Xiao-Fang Huang; Yan-Kuan Tian; Chang-Gui Pan; Xiang-Rong Xu (Marine Pollution Bulletin, 2026)

Arginine-rich hemp seed globulin-tannic acid non-covalent complexation: Structural compaction, enhanced antioxidant/emulsifying properties, and modulated digestibility - Yu Zhang; Xiao-Dong Tian; Zuo-Xing Di; Hai-Bo Jin; Guang-Xiang He; Suo-He Yang; Rong-Yue Zhang; Lei Ma; Xiao-Yan Guo; Peng-Wei Xu (Food Chemistry, 2026)

Fipronil and its metabolites in a tropical estuary: multi-compartment distribution, trophic transfer, and risk assessment - Yu-Han Xie; Can Huo; Zhi-Yan Wang; Shan-Shan Yao; Heng-Xiang Li; Yu Zhong; Xiao-Ping Huang; Xiang-Rong Xu (Marine Environmental Research, 2026)

Algicidal characteristics and mechanism of a newly identified bacterium Pseudomonas fulva EH5 against Microcystis aeruginosa - Rong Xiang; Tongpeng Jia; Geqi Zhang; Xue Sun; Nianjun Xu; Binghui Zheng (Journal of Hazardous Materials, 2026)

Heat stress modulates the size-dependent effects of aminated polystyrene particles on a marine diatom - Ting-Ting Xu; Zhen-Liang Li; Zhi-Yan Wang; Yu-Han Xie; Heng-Xiang Li; Xiang-Rong Xu (Journal of Hazardous Materials, 2026)

Perfluorohexane sulfonate (PFHxS)-induced energy metabolism disruption in Chlorella pyrenoidosa: Integrating physiological and transcriptomic insights - Biao Liao; Chang-Gui Pan; Feng-Jiao Peng; Jun-Jie Hu; Shan Liu; Ji-Xun Chen; Liu-Yi Wei; Xiang-Rong Xu; Kefu Yu (Environmental Pollution, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Impact of fulvic acid on copper exposure in Ulva prolifera: Integrative insights from growth, physiology, transcriptomics, and physico-chemical characteristics - Tongpeng Jia; Geqi Zhang; Yahe Li; Xinchuan Yang; Nianjun Xu; Rong Xiang (Journal of Hazardous Materials, 2026)

Interfacial engineering of core-shell Cu@Zn nanoclusters enables methane selective CO2 electroreduction via accelerated water dissociation - Wenlong Cao; Caiyu Chen; Hai Liu; Lei Yang; Tianlong Tan; Ruiyang Xu; Chengjian Ma; Tianyu Wang; Daniel Hedman; Shigeo Maruyama; Rong Xiang; Jue Wang; et al. (Chemical Engineering Journal, 2026)

Natural pyrite-enhanced co-culture system for simultaneous nitrate and ammonium removal under low C/N conditions: Mechanistic insights and real wastewater application - Kuang-di Xu; Pan He; Xiang-lin Liu; Lei Yu; Si-jia Li; Quan Wang; Rong-ping Chen; Ke Yin; Guang Guo; Wen-Jie Xu; Gong-De Wu (Bioresource Technology, 2026)

Synchronized organogenesis and fragment-specific behavioral recovery in Stichopus chloronotus inform artificial asexual culture and resource restoration of fissiparous sea cucumbers - Xinxin Huang; Xiang Hu; Mengjiao Liu; Ke Chen; Rong Cao; Fei Gao; Qiang Xu (Marine Biology, 2026)

Additive effects of heat and volatile organic compounds co-exposure on metabolic syndrome: evidence from petrochemical workers in China - Minhua Li; Rui Xu; Yilin Zhang; Shanshan Du; Rong Xu; Qing Zu; Zihu Lv; Wei Zheng; Weimin Ye; Jianjun Xiang (International Archives of Occupational and Environmental Health, 2026)

Unraveling antibiotic fate in a highly urbanized estuary: Spatiotemporal patterns, multi-media partitioning, and contaminant prioritization - Nian-Nian Wu; Shan Liu; Ru Xu; Qian-Yi Huang; Yun-Feng Pan; Heng-Xiang Li; Lang Lin; Rui Hou; Xiang-Rong Xu; Xiao-Ping Huang (Marine Pollution Bulletin, 2026)

Tectonically driven erosion with climatic modulation across the southern Tibetan Plateau: Insights from 10Be erosion rates - Jia-Qi Sun; Jin-Gen Dai; Xu Han; Matthew Fox; Guang-Sheng Ren; Zhi-Cheng Yu; Bo-Rong Liu; Xiang-Rui Liu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Distribution of plutonium in a ternary system of water-colloid-bentonite: Implications for radionuclide migration - Yan Liu; Chun Zhang; Yu Wang; Hui Xu; Rong Gong; Jianzheng Zang; Jianbo Liu; Xiang Zhou (Journal of Contaminant Hydrology, 2026)

Molecularly integrated dynamic chitosan network with topology-adaptive glucose/ROS responsiveness for coupled drug release and immunoregulation - Yuxiang Li; Sheng Dong; Ran Yu; Runjie Liu; Hengxi Xu; Hainuo Li; Wenbo Ming; Guochao Liao; Rong Zhang; Zhongqiu Liu; Wenxian Wang; Xiang Luo; et al. (Chemical Engineering Journal, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Three undescribed terpenoids from the aerial parts of Alstonia scholaris - Bing-ru Liu; Chun-xiang Xu; Dan Liu; Yue Feng; Rong-tao Li; Jin-dong Zhong (Phytochemistry Letters, 2026)

Paraphlomis wui (Lamiaceae), a new species from Chongqing, China - Jing-Chen Yuan; Jin-Fei Xiao; Wei-Bin Xu; Si-Rong Yi; Chun-Lei Xiang; Ya-Ping Chen (Kew Bulletin, 2026)

Release kinetics and environmental risks of TCPP from polyurethane foam microplastics: Insights from artificial seawater to natural estuarine water - Shan-Shan Yao; Yu-Han Xie; Zhi-Yan Wang; Shan Liu; Rui Hou; Lang Lin; Yu Zhong; Xiao-Ping Huang; Heng-Xiang Li; Xiang-Rong Xu (Environmental Pollution, 2026)

Magmatic source effects on Zircon Eu anomalies: Refining the Late Cretaceous–Eocene uplift of the Gangdese Arc, Southern Tibet - Guang-Sheng Ren; Jin-Gen Dai; Xiang-Rui Liu; Xu Han; Bo-Rong Liu; Jia-Qi Sun (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Spatial variations in soil carbon, nitrogen, and phosphorus stoichiometry across a northeast-southwest grassland transect in the monsoon-margin areas of China - Yuan Zhang; Na Rao; Bosen Yuan; Kai Wu; Xieping Xiang; Xumin Wei; Fangfang Xu; Jiusheng Ren; Yang Zhang; Ting Wu; Yun Zhang; Chao Huang; et al. (Journal of Soils and Sediments, 2026)

Development and validation of a copolymerized thiol-silica based DGT technique for the assessment of bioavailable As(Ⅲ) speciation - Yue Zeng; Zhennan Liu; Yajie Jiang; Yunqin Li; Wei Yu; Rong Yu; Xiang Xu; Meiling Xiao (Environmental Geochemistry and Health, 2026)

Integrating machine learning and prioritization to decipher the partitioning and risk of tire-derived chemicals in highly populated coastal regions - Nian-Nian Wu; Yuan Liu; Shan Liu; Ji-Xun Chen; Qin-Ge Zhou; Xiang-Rong Xu; Qing-Song Yang; Juan Ling; Jian-Liang Zhao (Water Research, 2026)

Lengthening vegetation carbon turnover time across China’s forests - Rong Ge; Xiaoli Ren; Honglin He; Guirui Yu; Li Zhang; Qian Xu; Mengyu Zhang; Shilong Piao; Kailiang Yu; Mathew Williams; Xiaobo Zhu; Shiyong Yu; et al. (Science Bulletin, 2026)

The emerging role of fatty acids as key bioactive components of Ganoderma lucidum spore oil in alleviating tumor progression - Qi-Jun Chen; Zi-Xuan Li; Guo-Cai Wang; Ting Xie; Guan-Di Xiao; Hui Xu; Jing Li; Xiang Luo; Yi-Fang Li; Lei Liang; Ju-Yan Liu; Yan-Ping Wu; et al. (Journal of Natural Medicines, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Cultivation strategies of Gracilariopsis lemaneiformis for balancing agar accumulation and environmental purification: The effect of 1-hydroxyethane-1,1,-diphosphonic acid - Dan Gu; Siqi Sun; Xue Sun; Rong Xiang; Hao Zhang; Nianjun Xu (Bioresource Technology, 2026)

Release kinetics and bioaccessibility of heavy metal from antifouling paint particles in simulated digestive fluids: An emerging threat to marine biota - Zhen-Liang Li; Ting-Ting Xu; Shan-Shan Yao; Heng-Xiang Li; Shan Liu; Rui Hou; Lang Lin; Zhi-Xin Ni; Qun Xie; Xiao-Ping Huang; Xiang-Rong Xu (Marine Pollution Bulletin, 2025)

Rainfall, seasonal variation, and stream type governing the multi-media fate and ecological risks of tire additives and their transformation products in mega-urban streams - Li-Ni Wei; Nian-Nian Wu; Ru Xu; Yuan Liu; Shan Liu; Hai-Yan Zhang; Zi-Tong Li; Yue-Hong Liu; Xiang-Rong Xu; Jian-Liang Zhao; Guang-Guo Ying (Water Research, 2025)

Multi-scale piezoresistive foam composed of graphene skeleton and vertical WS2 nanosheets designed for wearable detection/protection applications - Tengyue Song; Minxuan Xu; Yueqin Shi; Xin Li; Hang Wang; Zhe Kong; Suyu Sheng; Qi Zhang; Rong Xiang (Chemical Engineering Journal, 2025)

Sedimentary black carbon reveals shifting anthropogenic drivers in Lake Erhai Basin, southwest China - Xiang Kuai; Weiwei Sun; Min Xu; Yilan Liu; Rong Wang; Enlou Zhang (Environmental Pollution, 2025)

Regulatory mechanism of microplastics on arsenic bioavailability in a subtropical estuary, China - Yue Zeng; Yajie Jiang; Yunqin Li; Xiang Xu; Rong Yu; Wei Yu; Binxin Wu; Meiling Xiao (Science of The Total Environment, 2025)

Cytochrome P450-mediated biotransformation of octocrylene in Tetradesmus obliquus: Integrative insights from transcriptomics, proteomics, molecular docking, and density functional theory calculation - Jun-Jie Hu; Chang-Gui Pan; Xiang-Rong Xu; Feng-Jiao Peng; Shan Liu; Jiying Pei; Zhen-Zhu Liu; Hao Liang; Kefu Yu (Journal of Hazardous Materials, 2025)

Recovery of rare earth elements from sediments affected by mining activities - De-Xiang Xu; Xuan-Pu Cheng; Cui-Ling Huang; Xiao-Rui Liu; Can-Die Xie; Rong-Liang Qiu; Chang Liu; Mei-Na Guo; Jean-Louis Morel; Wen-Shen Liu; Ye-Tao Tang (Journal of Hazardous Materials, 2025)

Targeted and non-targeted analyses reveal trophic biomagnification of rubber-derived chemicals in an estuarine food web near China's largest rubber production region - Yuan Liu; Jia-Ming Zhou; Nian-Nian Wu; Shan Liu; Xiao-Liang Liao; Haijiang Wu; Lin Zhu; Heng-Xiang Li; Lang Lin; Rui Hou; Zhi-Hua Li; Xiang-Rong Xu; et al. (Journal of Hazardous Materials, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Low Nitrogen with Split Application Strategy Enhances Antioxidative Defense, Photosynthesis, and Enzymatic Activities to Waxy Maize Under Heat Stress - Song Xu-dong; Ahmad Irshad; Zhang Hui-min; Zhang Zhen-liang; Zhou Guang-fei; Chen Guo-qing; Mao Yu-xiang; Lu Hu-hua; Hao De-rong (Journal of Plant Growth Regulation, 2025)

Spatiotemporal distribution and priority assessment of steroids in the estuarine environment: Implications for environmental risk management - Ru Xu; Nian-Nian Wu; Shan Liu; Hui Chen; Qin-Wei Hao; Yong-Xia Hu; Bing Hong; Shen Yu; Xiang-Rong Xu (Marine Pollution Bulletin, 2025)

Exploring morphological heterogeneity of circulating tumor cells: machine learning-based approach for cell identification and prognostic implications - Peng-Xiang Wang; Yu-Chen Zhong; Bin Duan; Jian-Wen Cheng; Yun-Fan Sun; Wen-Jing Zheng; Kai-Qian Zhou; Yang Xu; Hai-Xiang Peng; Wei-Xiang Jin; Hai-Min Li; Xiao-Juan Sun; et al. (Science Bulletin, 2025)

Regulating the Cu-Ce interaction of CuCeOx/SAPO-34 catalysts to achieve a wide reaction temperature window for the collaborative synergistic removal of NOx and toluene at low temperatures and reaction mechanisms - Rong Liu; Xuehui Jia; Lin Li; Fengying Li; Xiang Tu; Weicheng Xu; Hansun Fang; Danping Li; Hong Huang; Chenglong Yu (Journal of Hazardous Materials, 2025)

Megastigmane glycosides from Heterosmilax yunnanensis and their neuroprotective activity - Rong-Rong Du; Wen-Jie Qin; Xiu-Mei Duan; Xu Zhang; Ya-Nan Yang; Jian-Shuang Jiang; Xiang Yuan; Pei-Cheng Zhang (Phytochemistry, 2025)

Climate warming will alter the impact of microplastics on the bioavailability of arsenic in a subtropical estuary - Yue Zeng; Yajie Jiang; Yunqin Li; Xiang Xu; Wei Yu; Rong Yu (Journal of Hazardous Materials, 2025)

Recent advances in low-temperature phase change materials for cold chain logistics - Xiang Yun Debbie Soo; Pin Jin Ong; Yee Kiat Zachary Lim; Suxi Wang; Warintorn Thitsartarn; FuKe Wang; Junhua Kong; Rong Ji; Nikodem Tomczak; Beng Hoon Tan; Pei Wang; Jianwei Xu; et al. (International Journal of Refrigeration, 2025)

Experimental study on defrosting multi outdoor units in turn for air source heat pump using hot gas - Xiang Li; Guoyuan Ma; Tianyu Lu; Lei Gao; Weilai Rong; Yuexuan Gong; Shuxue Xu (International Journal of Refrigeration, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Contamination, multimedia partitioning, and priority list of steroids and their metabolites in coastal regions of the Greater Bay Area, China - Qin-Ge Zhou; Shan Liu; Yuan Liu; Nian-Nian Wu; Qing-Song Yang; Heng-Xiang Li; Xiang-Rong Xu; Juan Ling (Process Safety and Environmental Protection, 2025)

Preparation of a La(OH)CO3/NiAl-LDHs interface junction photoinitiated activator: Excellent photoinitiated activity and the photoactive pathway for destruction of phenol in wastewater - Hui-Min Zhao; Wei-Peng Jia; Rui Dang; Xiang-Rong Ma; Yang Ma; Shuang-Yu Li; Xin Han; Nai-Cai Xu; Yu-Hong Kang; Yong Gao; Hua-Rui Hao; Rui Bai; et al. (Journal of Environmental Chemical Engineering, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Elevated CO2 alters antibiotic resistome in soil amended with sulfamethazine via chemical-organic fertilization - Fen Xu; Qian Xiang; Mei-Ling Xu; Laura J. Carter; Wen-Chao Du; Chun-Wu Zhu; Fu-Xun Ai; Ying Yin; Rong Ji; Hong-Yan Guo (Environmental Research, 2025)

Unveiling spatiotemporal distribution, partitioning, and transport mechanisms of tire additives and their transformation products in a highly urbanized estuarine region - Hai-Yan Zhang; Yue-Hong Liu; Li-Ni Wei; Rui-Qi Zhu; Jian-Liang Zhao; Shan Liu; Xiang-Rong Xu; Guang-Guo Ying (Science of The Total Environment, 2024)

Food web bioaccumulation model for ecological risk assessment of emerging organic pollutants in marine ecosystems: Principles, advances and challenges - Chuan-Sheng Sun; Rui Hou; Qian-Yi Huang; Zhi-Hua Li; Xiang-Rong Xu (Environmental Pollution, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Unraveling the toxicity mechanisms of nanoplastics with various surface modifications on Skeletonema costatum: Cellular and molecular perspectives - Ting-Ting Xu; Zhen-Liang Li; Heng-Xiang Li; Lang Lin; Rui Hou; Shan Liu; Tao Li; Eddy Y. Zeng; Ke-Fu Yu; Xiang-Rong Xu (Science of The Total Environment, 2024)

Fate and drivers of mariculture-derived microplastics from ponds to mangrove forests - Zhen Zhao; Yihua Wei; Yijin Wang; Gen Peng; Eddy Y. Zeng; Kefu Yu; Xiang-Rong Xu; Ruilong Li (Environmental Pollution, 2024)

Copper-ion-complexed palygorskite as a novel nanozyme with enhanced peroxidase-like activity for sensitive colorimetric sensing - Ping Chen; Hui Zhong; Xiao-rong Li; Tingting Zhang; Xiang Wang; Fang Hu; Yubo Yan; Jiaxing Xu; Meisheng Li (Applied Clay Science, 2024)

ALKBH5 SUMOylation-mediated FBXW7 m6A modification regulates alveolar cells senescence during 1-nitropyrene-induced pulmonary fibrosis - Se-Ruo Li; Ning-Ning Kang; Rong-Rong Wang; Meng-Die Li; Li-Hong Chen; Peng Zhou; De-Xiang Xu; Hui Zhao; Lin Fu (Journal of Hazardous Materials, 2024)

Early warning of urban heavy metal pollution based on PMF- MeteoInfo model combined with physicochemical properties of dust - Yue Zeng; Yajie Jiang; Yunqin Li; Xiang Xu; Xinying Zhang; Wei Yu; Rong Yu; Xinyu Liu (Stochastic Environmental Research and Risk Assessment, 2024)

Measuring ecosystem services and ecological sensitivity for comprehensive conservation in Giant Panda National Park - Cheng Li; Rong Hou; Ziqiang Bao; Wei Wu; Jacob R. Owens; Wenlei Bi; Qiang Xu; XiaoDong Gu; Zuofu Xiang; Dunwu Qi (Conservation Biology, 2024)
China announced the development of its first 5 national parks in 2021, the primary objective of which is to conserve the natural state and integrity of natural ecosystems. As such, ecosystem services and biodiversity levels are crucial assessment factors for the parks. For Giant Panda National Park (GPNP), we evaluated ecological sensitivity based on water and soil erosion and rocky desertification; ecosystem services based on headwater conservation, soil and water conservation, and biodiversity conservation; and presence of giant panda ( Ailuropoda melanoleuca ) and sympatric species (e.g., takin [ Budorcas taxicolor ], Asiatic black bear [ Ursus thibetanus ]) habitat suitability derived from niche modeling to identify the ecosystem status and assess ecological problems within the park. From our results, we proposed ecologically critical areas to target to meet the park's goals. The suitable habitat for pandas and sympatric species encompassed 62.98% of the park and occurred mainly in the Minshan Mountains. One quarter of the total area (25.67%) contained areas important for ecosystem services. Ecologically sensitive and extremely sensitive areas covered 88.78% of the park and were distributed mainly in Qionglaishan and Minshan Mountains. This coverage indicated that there was much habitat for pandas and sympatric species but that the ecosystems in GPNP are vulnerable. Therefore, ecologically critical areas encompassed all suitable habitats for all the species examined and areas important and extremely important to ecosystem service provision,ecologically sensitive and extremely sensitive areas, encompassed 15.17% of panda habitat, accounted for 16.37% of the GPNP area, and were distributed mainly in the Minshan Mountains. Our results indicated where conservation efforts should be focused in the park and that by identifying ecologically critical areas managers can provide targeted protection for wildlife habitat and ecosystems and effectively and efficiently protect the composite ecosystem. Additionally, our methods can be used to inform development of new national parks.

Tsaokoflavanols A1–J1: Flavanol-fatty alcohol hybrids with HPL inhibitory activity from Amomum tsao-ko - Tian-Rong Yang; Shi-Chao Huang; Yun-Fen Wang; Zai-Xiang Lou; Shao-Xing Dai; Li-Hua Su; Min Xu (Phytochemistry, 2024)

First insights into the bioaccumulation, biotransformation and trophic transfer of typical tetrabromobisphenol A (TBBPA) analogues along a simulated aquatic food chain - Chuan-Sheng Sun; Sheng-Wu Yuan; Rui Hou; Si-Qi Zhang; Qian-Yi Huang; Lang Lin; Heng-Xiang Li; Shan Liu; Yuan-Yue Cheng; Zhi-Hua Li; Xiang-Rong Xu (Journal of Hazardous Materials, 2024)

New insight into the bioaccumulation and trophic transfer of free and conjugated antibiotics in an estuarine food web based on multimedia fate and model simulation - Nian-Nian Wu; Shan Liu; Ru Xu; Qian-Yi Huang; Yun-Feng Pan; Heng-Xiang Li; Lang Lin; Rui Hou; Yuan-Yue Cheng; Xiang-Rong Xu (Journal of Hazardous Materials, 2024)

Developing a highly efficient, environmentally friendly and cost-effective copper sulfide semiconductor sponge for nuclear wastewater treatment under one sun - Wencai Bai; Mengjiao Liu; Kaifu Yu; Xin Cao; Jie Lian; Zhibin Zhao; Yong Xiang; Baoliang Xu; Tao Chen; Rong He; Nan Sun; Wenkun Zhu (Journal of Environmental Chemical Engineering, 2024)

Steroid metabolites as overlooked emerging contaminants: Insights from multimedia partitioning and source–sink simulation in an estuarine environment - Ru Xu; Shan Liu; Yun-Feng Pan; Nian-Nian Wu; Qian-Yi Huang; Heng-Xiang Li; Lang Lin; Rui Hou; Xiang-Rong Xu; Yuan-Yue Cheng (Journal of Hazardous Materials, 2024)

Voluntary running wheel exercise induces cognitive improvement post traumatic brain injury in mouse model through redressing aberrant excitation regulated by voltage-gated sodium channels 1.1, 1.3, and 1.6 - Dan Wang; Hui-Xiang Zhang; Guo-Ji Yan; Hao-Ran Zhao; Xiao-Han Dong; Ya-Xin Tan; Shan Li; Min-Nan Lu; Rong Mei; Li-Na Liu; Xu-Yang Wang; Yan-Bin Xiyang (Experimental Brain Research, 2024)
Traumatic brain injury (TBI) leads to disturbed brain discharge rhythm, elevated excitability, anxiety-like behaviors, and decreased learning and memory capabilities. Cognitive dysfunctions severely affect the quality of life and prognosis of TBI patients, requiring effective rehabilitation treatment. Evidence indicates that moderate exercise after brain injury decreases TBI-induced cognitive decline. However, the underlying mechanism remains unelucidated. Our results demonstrate that TBI causes cognitive impairment behavior abnormalities and overexpression of Nav1.1, Nav1.3 and Nav1.6 proteins inside the hippocampus of mice models. Three weeks of voluntary running wheel (RW) exercise treatments before or/and post-injury effectively redressed the aberrant changes caused by TBI. Additionally, a 10% exercise-conditioned medium helped recover cell viability, neuronal sodium current and expressions of Nav1.1, Nav1.3 and Nav1.6 proteins across cultured neurons after injury. Therefore, the results validate the neuroprotection induced by voluntary RW exercise treatment before or/and post-TBI. The RW exercise-induced improvement in cognitive behaviors and neuronal excitability could be associated with correcting the Nav1.1, Nav1.3, and Nav1.6 expression levels. The current study proves that voluntary exercise is an effective treatment strategy against TBI. The study also highlights novel potential targets for rehabilitating TBI, including the Navs proteins.

Artemisia selengensis Turcz. leaves extract ameliorates hyperuricemia in mice by inhibiting hepatic xanthine oxidase activity, modulating renal uric acid transporters, and improving metabolic disorders - Lin Xiang; Yuting Huang; Rong Li; Yexing Tao; Ting Wu; Siyi Pan; Xiaoyun Xu (Food Bioscience, 2023)

Tree species mixture effect on extracellular enzyme kinetics varies with enzyme type and soil depth in subtropical plantations - Xue-Li Jiang; Rong Mao; Zhong-Liang Li; Fu-Sheng Chen; Bin Xu; Jin He; Yu-Xin Huang; Xiang-Min Fang (Plant and Soil, 2023)

Vertical distribution and transport of microplastics in the urban atmosphere: New insights from field observations - Zhen Yuan; Cheng-Lei Pei; Heng-Xiang Li; Lang Lin; Rui Hou; Shan Liu; Kai Zhang; Ming-Gang Cai; Xiang-Rong Xu (Science of The Total Environment, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Thermochromic smart window utilizing passive radiative cooling for Self-Adaptive thermoregulation - Rong Zhang; Renzhi Li; Peng Xu; Wenhuan Zhong; Yifan Zhang; Zhenyang Luo; Bo Xiang (Chemical Engineering Journal, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Catalytic probes based on aggregation-induced emission-active Au nanoclusters for visualizing MicroRNA in living cells and in vivo - Wenhao Shu; Xuetao Zhang; Hongmei Tang; Linna Wang; Manxiao Cheng; Jingwen Xu; Rong Li; Xiang Ran (Analytica Chimica Acta, 2023)

“On-off”controlled H2 evolution and O2 evolution upon NH3BH3 hydrolysis resp·H2O2 decomposition on Pt/ZIF-67 - Qi Rong; Wenkai Huang; Fuhua Xu; Yanlan Wang; Changlong Wang; Xiang Liu (Fuel, 2023)

An effective tool for tracking steroids and their metabolites at the watershed level: Combining fugacity modeling and a chemical indicator - Ru Xu; Shan Liu; Hui Chen; Qin-Wei Hao; Yong-Xia Hu; Heng-Xiang Li; Lang Lin; Rui Hou; Bing Hong; Shen Yu; Xiang-Rong Xu (Environmental Pollution, 2023)

The mechanisms of rapid seed germination in Caragana species adapted to low mean annual precipitation - Shi-Hua Qi; Guang-Qian Yao; Md. Mahadi Hasan; Hui Jiang; Xu-Dong Liu; Zheng-Fei Nie; Xia-Yi Zhang; Ya-Xian Du; Xue-Qian Tian; Feng-Ping Li; Xue-Rong Li; Xiang-Wen Fang (Trees, 2023)

Free and conjugated forms of metabolites are indispensable components of steroids: The first evidence from an estuarine food web - Shan Liu; Ru Xu; Yun-Feng Pan; Qian-Yi Huang; Nian-Nian Wu; Heng-Xiang Li; Lang Lin; Rui Hou; Xiang-Rong Xu (Water Research, 2023)

Elevated CO2 alleviated the dissemination of antibiotic resistance genes in sulfadiazine-contaminated soil: A free-air CO2 enrichment study - Meiling Xu; Qian Xiang; Fen Xu; Lei Guo; Laura J. Carter; Wenchao Du; Chunwu Zhu; Ying Yin; Rong Ji; Xiaozhi Wang; Hongyan Guo (Journal of Hazardous Materials, 2023)

Adsorption of heavy metals on biodegradable and conventional microplastics in the Pearl River Estuary, China - Min Shi; Qun Xie; Zhen-Liang Li; Yun-Feng Pan; Zhen Yuan; Lang Lin; Xiang-Rong Xu; Heng-Xiang Li (Environmental Pollution, 2023)

Risk assessment and environmental determinants of urinary phthalate metabolites in pregnant women in Southwest China - Nian Wu; Lin Tao; Kunming Tian; Xia Wang; Caidie He; Songlin An; Yingkuan Tian; Xiang Liu; Wei Chen; Haonan Zhang; Pei Xu; Dengqing Liao; et al. (Environmental Science and Pollution Research, 2023)

Expanded polystyrene buoys as an important source of hexabromocyclododecanes for aquatic ecosystem: Evidence from field exposure with different substrates - Yun-Feng Pan; Shan Liu; Heng-Xiang Li; Lang Lin; Rui Hou; Yuan-Yue Cheng; Xiang-Rong Xu (Environmental Pollution, 2023)

Sn2P2S6: A lead-free reversible thermochromic ferroelectric with high near-infrared reflectance - Meixia Wu; Xiao Zhou; Xihui Liang; Yifeng Han; Yonghong Li; Xingan Jiang; Xueyun Wang; Yisheng Chai; Xiang Zhou; Hui Yang; Dan Lin; Ping Xu; et al. (Chemical Engineering Journal, 2023)

Carbonate nanophase guided by terminally functionalized polyisoprene leading to a super tough, recyclable and transparent rubber - Mo-Kun Chen; Yi-Hai Zhao; Rong Zhang; Ying Yang; Jian Cao; Mao-Zhu Tang; Guangsu Huang; Yun-Xiang Xu (Chemical Engineering Journal, 2023)

Proteomic analysis and identification reveal the anti-inflammatory mechanism of clofazimine on lipopolysaccharide-induced acute lung injury in mice - Bo Yang; Zhan Gao; Qi-Shuang Li; Xiang-Ye Zhang; Lan Song; Yi-Ni Wang; Xin-Yue Wang; Lin-Lin Ji; Hong-Liang Xu; Hui Xie; Fu-Kai Feng; Xiao-Ping Li; et al. (Inflammation Research, 2022)

Microplastic prevalence in marine fish from onshore Beibu Gulf, South China Sea - Jayamini Bimali Koongolla; Lang Lin; Chang-Ping Yang; Yun-Feng Pan; Heng-Xiang Li; Shan Liu; Xiang-Rong Xu (Frontiers in Marine Science, 2022)
In recent years, microplastics have been widely detected in marine fish and may pose potential risks to fish and human health. Even though microplastic pollution is a critical issue, it represents as yet non-quantified threat for some context in the marine environment. In this study, 271 individuals comprising 32 species of marine fish collected from Beibu Gulf were examined for microplastic prevalence, with an aim to provide data on the abundance, physical classification, and chemical characterization of microplastics in the great bay along South China Sea. The results showed that the occurrence rate of microplastics was 93.7%, and the average abundance of microplastics was 1.02 ± 0.18 items per individual (ranging from 0.03 to 4.00 items per individual). Microplastic accumulation was observed with a great variation in different species, body sizes, living habitats, and feeding habits of marine fishes. The dominant polymers identified by μ-FTIR were polyethylene terephthalate and polypropylene. Fibers, smaller sizes (<1 mm), and transparent color were the major characteristics of the detected microplastics, which might be important factors affecting the bioaccumulation. The present study revealed that microplastics in marine fish is a widespread issue in onshore Beibu Gulf.

Genetic Diversity Analysis of Sugarcane (Saccharum spp. hybrids) Among High-Sucrose Clones of GT Series and Commonly Used Parents by Using Microsatellite Markers in Guangxi, China - Hai-Rong Huang; Yi-Jing Gao; Mukesh Kumar Malviya; Krishan K. Verma; Manoj Kumar Solanki; Yu-Xin Huang; Xiang Li; Yuchi Deng; Jing Yan; Shi-Yun Tang; Lun-Wang Wang; Lin Xu (Sugar Tech, 2022)

Characteristics of expanded polystyrene microplastics on island beaches in the Pearl River Estuary: abundance, size, surface texture and their metals-carrying capacity - Qun Xie; Heng-Xiang Li; Lang Lin; Zhen-Liang Li; Jian-sheng Huang; Xiang-Rong Xu (Ecotoxicology, 2021)

FgPal1 regulates morphogenesis and pathogenesis in Fusarium graminearum - Jinrong Yin; Chaofeng Hao; Gang Niu; Wei Wang; Guanghui Wang; Ping Xiang; Jin‐Rong Xu; Xue Zhang (Environmental Microbiology, 2020)
Summary Ascospores are the primary inoculum in Fusarium graminearum , a causal agent of wheat head blight. In a previous study, FgPAL1 was found to be upregulated in the Fgama1 mutant and important for ascosporogenesis. However, the biological function of this well‐conserved gene in filamentous ascomycetes is not clear. In this study, we characterized its functions in growth, differentiation and pathogenesis. The Fgpal1 mutant had severe growth defects and often displayed abnormal hyphal tips. It was defective in infectious growth in rachis tissues and spreading in wheat heads. The Fgpal1 mutant produced conidia with fewer septa and more nuclei per compartment than the wild type. In actively growing hyphal tips, FgPal1‐GFP mainly localized to the subapical collar and septa. The FgPal1 and LifeAct partially co‐localized at the subapical region in an interdependent manner. The Fgpal1 mutant was normal in meiosis with eight nuclei in developing asci but most asci were aborted. Taken together, our results showed that FgPal1 plays a role in maintaining polarized tip growth and coordination between nuclear division and cytokinesis, and it is also important for infectious growth and developments of ascospores by the free cell formation process.

Physiological and transcriptional response to heat stress in heat-resistant and heat-sensitive maize (Zea mays L.) inbred lines at seedling stage - De-Chuan Wu; Jia-Fei Zhu; Zhong-Ze Shu; Wei Wang; Cheng Yan; Shan-Bin Xu; De-Xiang Wu; Cheng-Yu Wang; Zhao-rong Dong; Genlou Sun (Protoplasma, 2020)

Preparation and In vitro Evaluation of FDM 3D-Printed Ellipsoid-Shaped Gastric Floating Tablets with Low Infill Percentages - Di Chen; Xiang-Yu Xu; Rui Li; Gen-Ao Zang; Yue Zhang; Ming-Rui Wang; Meng-Fei Xiong; Jia-Rui Xu; Ting Wang; Hui Fu; Qin Hu; Bin Wu; et al. (AAPS PharmSciTech, 2020)

Angiogenesis in pancreatic cancer: current research status and clinical implications - Shuo Li; Hua-Xiang Xu; Chun-Tao Wu; Wen-Quan Wang; Wei Jin; He-Li Gao; Hao Li; Shi-Rong Zhang; Jin-Zhi Xu; Zi-Hao Qi; Quan-Xing Ni; Xian-Jun Yu; et al. (Angiogenesis, 2019)

Identification and genetic mapping for rht-DM, a dominant dwarfing gene in mutant semi-dwarf maize using QTL-seq approach - Qian Chen; Jun Song; Wen-Ping Du; Li-Yuan Xu; Yun Jiang; Jie Zhang; Xiao-Li Xiang; Gui-Rong Yu (Genes & Genomics, 2018)

Nortirucallane A, a new tirucallane-type nortriterpenoid isolated from Lonicerae japonicae flos - Xu Wang; Jing Zhang; Ya-qun Li; Bao-xiang Du; Qi-hui Sun; Yun-jiao Cao; Hai-qiang Jiang; Yu-hong Liu; Hong-lei Zhou; Rong Rong (Natural Product Research, 2017)

Seasonal variations of organic carbon and nitrogen in the upper basins of Yangtze and Yellow Rivers - Xiang-ying Li; Yong-jian Ding; Tian-ding Han; Jian-zhong Xu; Shi-chang Kang; Qing-bai Wu; Mika Sillanpää; Zhong-bo Yu; Cong-rong Yu (Journal of Mountain Science, 2017)

Local adaptation shapes pattern of mitochondrial population structure in Sebastiscus marmoratus - Sheng-Yong Xu; Dian-Rong Sun; Na Song; Tian-Xiang Gao; Zhi-Qiang Han; Bo-Nian Shui (Environmental Biology of Fishes, 2017)

Lower functional connectivity of default mode network in cognitively normal young adults with mutation of APP, presenilins and APOE ε4 - Yun Yan Su; Xiao Dong Zhang; U. Joseph Schoepf; Akos Varga-Szemes; Andrew Stubenrauch; Xue Liang; Li Juan Zheng; Gang Zheng; Xiang Kong; Qiang Xu; Shou Ju Wang; Rong Feng Qi; et al. (Brain Imaging and Behavior, 2017)

A Volumetric and Functional Connectivity MRI Study of Brain Arginine-Vasopressin Pathways in Autistic Children - Xiao-Jing Shou; Xin-Jie Xu; Xiang-Zhu Zeng; Ying Liu; Hui-Shu Yuan; Yan Xing; Mei-Xiang Jia; Qing-Yun Wei; Song-Ping Han; Rong Zhang; Ji-Sheng Han (Neuroscience Bulletin, 2017)

Performance improvement of raw water pretreatment process with pre-inoculation biofilm: feasibility and limiting factors - Guang-feng Yang; Li-juan Feng; Cai-rong Guo; Tian Xia; Xiang-yang Xu; Liang Zhu (Biodegradation, 2017)

Identification and Characterization of the Lysine-Rich Matrix Protein Family in Pinctada fucata: Indicative of Roles in Shell Formation - Jian Liang; Jun Xie; Jing Gao; Chao-Qun Xu; Yi Yan; Gan-Chu Jia; Liang Xiang; Li-Ping Xie; Rong-Qing Zhang (Marine Biotechnology, 2016)

Spatial and Vertical Distribution of Dechlorane Plus in Mangrove Sediments of the Pearl River Estuary, South China - Yu-Xin Sun; Zai-Wang Zhang; Xiang-Rong Xu; Qin-Wei Hao; Yong-Xia Hu; Xiao-Bo Zheng; Xiao-Jun Luo; Zeng-Hui Diao; Bi-Xian Mai (Archives of Environmental Contamination and Toxicology, 2016)

The LXR ligand GW3965 inhibits Newcastle disease virus infection by affecting cholesterol homeostasis - Xiang-xiang Sheng; Ying-jie Sun; Yuan Zhan; Yu-rong Qu; Hua-xia Wang; Miao Luo; Ying Liao; Xu-sheng Qiu; Chan Ding; Hong-jie Fan; Xiang Mao (Archives of Virology, 2016)

Heat shock protein 70 inhibits cardiomyocyte necroptosis through repressing autophagy in myocardial ischemia/reperfusion injury - Xiaojuan Liu; Chao Zhang; Chi Zhang; Jingjing Li; Wanwan Guo; Daliang Yan; Chen Yang; Jianhua Zhao; Tian Xia; Yuqing Wang; Rong Xu; Xiang Wu; et al. (In Vitro Cellular & Developmental Biology - Animal, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Developing a salinity-based approach for the evaluation of DIN removal rate in estuarine ecosystems - Yiguo Hong; Shuailong Wang; Xiang-Rong Xu; Jiapeng Wu; Ling Liu; Weizhong Yue; Meilin Wu; Youshao Wang (Ecotoxicology, 2015)

Geographical distribution and risk assessment of persistent organic pollutants in golden threads (Nemipterus virgatus) from the northern South China Sea - Qing Hao; Yu-Xin Sun; Xiang-Rong Xu; Zi-Wei Yao; You-Shao Wang; Zai-Wang Zhang; Xiao-Jun Luo; Bi-Xian Mai (Ecotoxicology, 2015)

Ecotoxicity of two organophosphate pesticides chlorpyrifos and dichlorvos on non-targeting cyanobacteria Microcystis wesenbergii - Kai-Feng Sun; Xiang-Rong Xu; Shun-Shan Duan; You-Shao Wang; Hao Cheng; Zai-Wang Zhang; Guang-Jie Zhou; Yi-Guo Hong (Ecotoxicology, 2015)

Heavy metals in wild marine fish from South China Sea: levels, tissue- and species-specific accumulation and potential risk to humans - Jin-Ling Liu; Xiang-Rong Xu; Zhen-Hua Ding; Jia-Xi Peng; Ming-Hua Jin; You-Shao Wang; Yi-Guo Hong; Wei-Zhong Yue (Ecotoxicology, 2015)

Heavy metal and organic contaminants in mangrove ecosystems of China: a review - Zai-Wang Zhang; Xiang-Rong Xu; Yu-Xin Sun; Shen Yu; Yong-Shan Chen; Jia-Xi Peng (Environmental Science and Pollution Research, 2014)

A comparative study of bioactive secondary metabolite production in diploid and tetraploid Echinacea purpurea (L.) Moench - Chuan-gui Xu; Tie-xin Tang; Rong Chen; Chun-hui Liang; Xiang-yu Liu; Chuan-long Wu; Yue-sheng Yang; De-po Yang; Hong Wu (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

Estrogen receptor α gene PvuII polymorphism and coronary artery disease: a meta-analysis of 21 studies - Jie Ding; Hui Xu; Xiang Yin; Fu-rong Zhang; Xiao-ping Pan; Yi-an Gu; Jun-zhu Chen; Xiao-gang Guo (Journal of Zhejiang University-SCIENCE B, 2014)

Effect of lithology and structure on seismic response of steep slope in a shaking table test - Han-xiang Liu; Qiang Xu; Yan-rong Li (Journal of Mountain Science, 2014)

Application of Endobronchial Ultrasound-Guided Transbronchial Needle Aspiration in the Management of Mediastinal and Hilar Lymphadenopathy Without Intrapulmonary Mass: Experience from the Largest Cancer Center of Southern China - Guang-yu Luo; Pei-qiang Cai; Jie-hua He; Jian-jun Li; Yin Li; Hong-bo Shan; Rong Zhang; Xiao-yan Gao; Xiang-ming Lao; Guo-liang Xu (Cell Biochemistry and Biophysics, 2013)

An overview of studies on psychological well-being in children born following assisted reproductive technologies - Qi-tao Zhan; Pei-pei Pan; Xiang-rong Xu; Hang-ying Lou; Yi-yun Lou; Fan Jin (Journal of Zhejiang University-SCIENCE B, 2013)

Genetic structure and association mapping of cold tolerance in improved japonica rice germplasm at the booting stage - Di Cui; Chang-ying Xu; Cui-feng Tang; Chun-gang Yang; Teng-qiong Yu; Xin-xiang A; Gui-lan Cao; Fu-rong Xu; Jun-guo Zhang; Long-zhi Han (Euphytica, 2013)

Persistence and intergenerational transmission of differentially expressed genes in the testes of intracytoplasmic sperm injection conceived mice - Li-ya Wang; Ning Wang; Fang Le; Lei Li; Le-jun Li; Xiao-zhen Liu; Ying-ming Zheng; Hang-ying Lou; Xiang-rong Xu; Xiao-ming Zhu; Yi-min Zhu; He-feng Huang; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

Nitrate and nitrite content in bottled beverages by ion-pair high-performance liquid chromatography - Yang Song; Gui-Fang Deng; Xiang-Rong Xu; Yong-Hong Chen; Feng Chen; Hua-Bin Li (Food Additives & Contaminants Part B-Surveillance, 2013)

Phenolic Compounds and Bioactivities of Pigmented Rice - Gui-Fang Deng; Xiang-Rong Xu; Yuan Zhang; Dan Li; Ren-You Gan; Hua-Bin Li (Critical Reviews in Food Science and Nutrition, 2013)

Normal epigenetic inheritance in mice conceived by in vitro fertilization and embryo transfer - Lei Li; Fang Le; Li-ya Wang; Xiang-rong Xu; Hang-ying Lou; Ying-ming Zheng; Jiang-zhong Sheng; He-feng Huang; Fan Jin (Journal of Zhejiang University-SCIENCE B, 2011)

PpGalNacT2 participating in vanadium-induced HL-60 cell differentiation - Yuan Gao; You Bin Tu; Yi Guo; Ling Yan Yang; Xiang Hong Guo; Lan Xu; Zheng Rong Xu; Shi Liang Wu (Molecular Biology Reports, 2011)

Methylobacterium soli sp. nov. a methanol-utilizing bacterium isolated from the forest soil - Yan-Ru Cao; Qian Wang; Rong-Xian Jin; Shu-Kun Tang; Yi Jiang; Wen-Xiang He; Hang-Xian Lai; Li-Hua Xu; Cheng-Lin Jiang (Antonie van Leeuwenhoek, 2011)

Effects of immune activation on the retrieval of spatial memory - Zhen-Bo Huang; Hao Wang; Xiu-Rong Rao; Tao Liang; Jing Xu; Xiang-Sheng Cai; Guo-Qing Sheng (Neuroscience Bulletin, 2010)

Immunosuppressive effects of mesenchymal stem cells in collagen-induced mouse arthritis - Fei Mao; Wen-Rong Xu; Hui Qian; Wei Zhu; Yong-Min Yan; Qi-Xiang Shao; Hua-Xi Xu (Inflammation Research, 2010)

Saponin fraction from Astragalus membranaceus roots protects mice against polymicrobial sepsis induced by cecal ligation and puncture by inhibiting inflammation and upregulating protein C pathway - Xing-hua Gao; Xian-xiang Xu; Rong Pan; Ying Li; Yu-bin Luo; Yu-feng Xia; Kazuya Murata; Hideaki Matsuda; Yue Dai (Journal of Natural Medicines, 2009)

Effect of the untranslated region and signal peptide sequence of the insecticidal gene from Pseudomonas pseudoalcaligenes on the activity of its expression products in tobacco - Min Huang; Da-Xu Li; Wen-Liang Xiang; Hao Chen; Jian-Hua Guo; Jian Zhao; Jie Zhang; Zhi-Rong Yang; Qun Sun (World Journal of Microbiology and Biotechnology, 2009)

Depressive-like behavior in mice recently recovered from motor disorders after 3-nitropropionic acid intoxication - Xiao-Min Li; Bing-Gen Zhu; Sha Ma; Wei Zhou; Zheng Wei; Yu-Xiang Zheng; Xu-Dong Zhao; Rong-Shen Zhu (Neuroscience Bulletin, 2008)

BRD2 is one of BRD7-interacting proteins and its over-expression could initiate apoptosis - Ming Zhou; Xiao-Jie Xu; Hou-De Zhou; Hua-Ying Liu; Jia-Jin He; Xiao-Ling Li; Cong Peng; Wei Xiong; Song-Qing Fan; Jian-Hong Lu; Jue Ouyang; Shou-Rong Shen; et al. (Molecular and Cellular Biochemistry, 2006)

Novel CACNA1S mutation causes autosomal dominant hypokalemic periodic paralysis in a Chinese family - Qiufen Wang; Mugen Liu; Chunsheng Xu; Zhaohui Tang; Yuhua Liao; Rong Du; Wei Li; Xiaoyan Wu; Xu Wang; Ping Liu; Xianqin Zhang; Jianfang Zhu; et al. (Journal of Molecular Medicine, 2005)

The promoter of a rice glycine-rich protein gene, Osgrp-2, confers vascular-specific expression in transgenic plants - Zong-Zhi Liu; Jian-Long Wang; Xun Huang; Wei-Hui Xu; Zhao-Ming Liu; Rong-Xiang Fang (Planta, 2003)